Modelling the Health Information System in Slovenia — Operative, Construction and Implementation Aspects - Stanimirovic, Dalibor (International Journal of Engineering Business Management, 2015)
Fragmented and non-interoperable information systems (ISs) generate poor quality information and adversely affect the provision of healthcare services and the management of the Slovenian healthcare system. Advanced implementation of the eHealth project, encompassing the construction of a national health information system (HIS), could play a pivotal role in overcoming these challenges, which significantly compromise further development of the Slovenian healthcare system. This paper initially presents a review of the recent developments concerning HIS and identifies its main operative deficiencies. Subsequently, the paper outlines the construction of a 3LGM2-based conceptual HIS model and provides generally applicable recommendations and guidelines for effective implementation of HISs. This research employs a single explanatory/exploratory case study design, while the validation of the hypothesized constructs was undertaken through structured interviews with 15 prominent experts from the Slovenian healthcare system. The findings provide valuable insight into the operative, construction, and implementation aspects of HIS, which can, subject to proficient coordination with other ecosystem factors and pending structural reforms, ensure better utilization of public healthcare resources and provide tangible public health benefits.